Pengaruh Iklan,Atribut Produk, dan Harga terhadap Keputusan Pembelian (Studi pada Pembeli dan Pengguna OPPOSmartphone di Kota Semarang) - Nasha Farahna Sungkar; Agung Budiatmo (Universitas Diponegoro, 2016)
The increasingly fierce competition among the smartphone manufacturers are competingto launch products with a variety of advantages. One of the products discussed are crowdedsmartphone OPPO Smartphone. In the face of tight business competition Smartphone OPPO needto influence consumers to choose and buy products OPPO Smartphone. Many factors influenceconsumers in making a purchase, such as advertising, product attributes, and price.This study aims to determine the effect of advertising, product attributes, and prices onproduct purchasing decisions OPPO Smartphone partially or simultaneously. This type ofresearch is explanatory research. Primary data used questionnaires distributed to the publicSemarang central mobile phone sales Matahari Mall Semarang who have bought and used theproducts OPPO Smartphone as many as 100 people. In the analysis used validity and reliability,the correlation coefficient, the coefficient of determination, cross tabulations, simple and multipleregression analysis and significance test (t test and F) with SPSS 21.The results showed a variable adverstising positive influence on purchasing decisions by23.1%. Variable product attributes positive influence on purchasing decisions by 17.9%. Andvariable price positive influence on purchasing decisions by 23.6%. Through research also foundthat the three independent variables simultaneously significant positive effect on purchasingdecisions and are able to explain 46.9% of purchasing decisions.Based on the results of the study, the researchers suggested that OPPO Smartphonemanufacturers maximize advertising concept which will be displayed in order to load the excessproduct is clearly and understood by consumers. And to attract more consumers, manufacturersare expected to innovate on product design to make it look more attractive than other smartphonebrands. Manufacturers are also expected not to take profit too large, so that product prices moreaffordable by the consumers' income. Moreover, manufacturers are expected to improve thequality and specifications of the products to be robust, as the society of this era that requiressophisticated smartphones.